Disruptive plasma simulations in EAST including 3D effects. (9th September 2019) - Chen, S.L.; Villone, F.; Sun, Y.W.; Rubinacci, G.; Ventre, S.; Xiao, B.J.; Luo, Z.P.; Guo, Y.; Wang, H.H.; Shi, T.H.; Chen, D.L.; Liu, L.; et al.
Abstract: A simulation of a disruption in the experimental advanced superconducting tokamak (EAST) is carried out with the CarMa0NL code and the results are successfully compared with the experimental data. The fundamental role of three-dimensional (3D) features of conducting structures surrounding the plasma is demonstrated and is fully accounted for in simulations. The results demonstrate that the currents measured by Rogowski coils placed around the supports of in-vessel plasma facing components (PFCs) are largely due to eddy currents induced by the plasma motion and current decay, with a relatively small contribution coming from the currents directly injected from the plasma into the structures (halo currents).